2012
DOI: 10.4172/2155-9899.s5-005
|View full text |Cite
|
Sign up to set email alerts
|

Development of Proteasome Inhibitors as Therapeutic Drugs

Abstract: The proteasome is a multi-unit enzyme complex found in the cytoplasm and nucleus of all eukaryotic cells and is responsible for degradation of unneeded or damaged intracellular proteins by proteolysis, a chemical reaction that breaks peptide bonds. Proteasome inhibition presents a promising approach to cancer therapy by targeting the proteasome function in tumor cells. Delineating the success of bortezomib in the treatment of multiple myeloma and mantle cell lymphoma, this review explores various proteasome in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 35 publications
(51 reference statements)
0
22
0
Order By: Relevance
“…The two FDA-approved proteasome inhibitors, bortezomib and carfilzomib, both target the core proteolytic subunits PSMB5, PSMB6, and PSMB7 (38). The noncatalytic subunit PSMB4 represents a novel potential target as it plays an important role in regulating the assembly of the proteasome (28,29), and, thus, by inhibiting its function and proteasome assembly one could potentially prevent the catalytic activity of all three proteolytic subunits.…”
Section: Discussionmentioning
confidence: 99%
“…The two FDA-approved proteasome inhibitors, bortezomib and carfilzomib, both target the core proteolytic subunits PSMB5, PSMB6, and PSMB7 (38). The noncatalytic subunit PSMB4 represents a novel potential target as it plays an important role in regulating the assembly of the proteasome (28,29), and, thus, by inhibiting its function and proteasome assembly one could potentially prevent the catalytic activity of all three proteolytic subunits.…”
Section: Discussionmentioning
confidence: 99%
“…It plays a vital role in degrading most short-lived intra-cellular proteins that regulate a wide spectrum of events in the cell such as cell cycle, cell differentiation, cell death, DNA repair, transcription, signal transduction, morphogenesis, metabolism and antigen (Ag) presentation. The proteasome functions as the main nonlysosomal endoprotease enzyme complex within the nucleus and cytoplasm of all eukaryotic cells in order to eliminate damaged and abnormal proteins to ensure intracellular protein quality [1]. …”
Section: The Ubiquitin-proteasome System and Its Physiologic Relevancementioning
confidence: 99%
“…3 Of the 55 most lethal genes identified, functional testing in HMCLs and non-MM cell lines indicated that proteasome subunits (A1, A3, A4, A6, C3, C4 and C5), MCL1, RRM1, USP8, TNK2, CKAP5, IK, KIF11, WBSCR22 and XPO1 are selectively vulnerable in myeloma. 3 Proteasome inhibitors have been developed and are commonly used in the clinic, 4 however, drugs that target the other potentially interesting therapeutic targets are not yet available.…”
Section: Introductionmentioning
confidence: 99%